Assessment of Leptin Gene Polymorphism rs2060713 in Psoriasis Vulgaris. (28th January 2014) - Karpouzis, Anthony; Tripsianis, Gregory; Gatzidou, Elisavet; Veletza, Stavroula
Abstract : Psoriasis is a lifelong disorder characterized by approximately 8-fold reduction of the duration of normal skin keratinocyte cell cycle and 2-fold increase of the number of dividing cells. Multiple genes, several environmental factors, and immune system alterations are involved in the pathogenesis of psoriasis. Hyperleptinemia is associated with psoriasis and leptin acts as an angiogenic factor. Angiogenetic processes precede the epidermal hyperplasia in psoriasis, indicating possible involvement of leptin in the pathogenesis of psoriasis. Leptin gene polymorphisms and their association with psoriasis have been given very little attention. We present a study of the rs2060713C/T genetic polymorphism in the pathogenesis of psoriasis vulgaris in 263 vulgaris patients and 252 unrelated matched healthy controls. No statistically significant differences were observed between patients and controls. A statistically nonsignificant trend was observed in males with the early onset type of psoriasis (11.1% C/T in patients versus 5.6% in controls) and in females with the late onset type of the disease (12.8% C/T in patients versus 3.3% in controls). Still, there is no hard evidence on correlation of psoriasis vulgaris with this polymorphism. Possible association with specific forms of the disease and either gender needs further investigation in larger studies.